Conservação de ambientes campestres no Cerrado e implicações para riqueza de espécies de aves - Bonanomi, Juliana (2018)
Brazil is recognized worldwide for its biological diversity, and in recent decades has become a world competitor in agricultural production. These make public policies for the conservation of natural habitats strategic and include all the diversity of habitats and species that exist. Understanding how the high diversity of species is related to the availability of habitats is important because it gives us subsidies for efficient strategic actions in the conservation of species. In the first chapter, we evaluate how the richness of birds, which are extremely sensitive to habitat loss, responds to the composition of the landscape. The result showed that there is an increase of species with the increase of vegetation cover of forests and grasslands. In the second chapter, we tried to understand how the Brazilian laws act for the conservation of the natural habitats; our results show that the Brazilian environmental law favors the conservation of forests in the Cerrado to the detriment of grasslands. With this, our results show that grasslands restricted species are losing their natural habitat. Finally, we must recognize that Brazil is at a crucial moment between agricultural increase and environmental preservation. Environmental laws urgently need to have strategies for the conservation of grasslands environments, or we will lose much of the biodiversity in the Cerrado Biome.